Analysis of the High Quality Development of Sports and Leisure Industry in Beijing from the Perspective of National Fitness - Ze Li (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The rise of national fitness as a national strategy shows that the development mode of sports in China is changing from the traditional "gold medal sports" to "sports for all", which is a significant change in the development of sports industry in China. In this context, the reasonable development and allocation of sports resources can provide multi-level, personalized and accurate fitness service needs for the public. In recent years, the national related departments have issued an "about speed up the development of fitness and leisure industry guidance", "about promoting the national fitness and sports consumption opinion" to promote the development of high-quality sports industry policy documents, such as standing in the perspective of national level will launch sports leisure industry as an important part of "healthy China" strategy. The rapid development of service industries such as fitness, leisure and competition performance have to a large extent optimized the original structure of the sports industry, and with the proposed plan to cultivate the sports and leisure industry into a pillar industry of the sports industry, it provides a new growth point for the development of China's economy. The sports and leisure industry specifically refers to a kind of goods and services related to leisure and sports activities. The development of the sports and leisure industry has become a new growth pole in the development of the sports industry, which is closely related to the development of regional economy, the consumption level of residents and the awareness of sports and fitness. In recent years, the overall development momentum of Beijing's leisure sports industry is good, but there are still a lot of problems, which have caused a certain impact on the healthy development of the sports and leisure industry. In order to better promote the development of high quality of the Beijing municipal sports leisure industry, the implementation of the strategy for overall fitness to lay a good foundation, this paper will stand in the perspective of the national fitness, the present situation of the development of the sports leisure industry in Beijing is analyzed and the research, and on the basis of the high quality of leisure sports industry development path of Beijing.